2014
DOI: 10.3892/ol.2014.2304
|View full text |Cite
|
Sign up to set email alerts
|

Coexistence of t(15;17) and t(15;16;17) detected by fluorescence in situ hybridization in a patient with acute promyelocytic leukemia: A case report and literature review

Abstract: Acute promyelocytic leukemia (APL) is characterized by the t(15;17)(q22;q21), which results in the fusion of the promyelocytic leukemia (PML) gene at 15q22 with the retinoic acid α-receptor (RARA) gene at 17q21. The current study presents the case of a 54-year-old female with APL carrying the atypical PML/RARA fusion signal due to a novel complex variant translocation t(15;16;17)(q22;q24;q21), as well as the classical PML/RARA fusion signal. Subsequent array comparative genomic hybridization revealed somatic, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…There are a number of studies concerning the alternate translocation in APL; however, little is still known about the complex variant translocations in APL (22,23). Both 4, 15, 17, and 15, 16, 17 translocations have been described by other authors (4,6,22,23), but the translocation found in our patient involving four chromosomes 4, 15, 16, and 17 has not been reported before.…”
Section: Discussionmentioning
confidence: 48%
See 2 more Smart Citations
“…There are a number of studies concerning the alternate translocation in APL; however, little is still known about the complex variant translocations in APL (22,23). Both 4, 15, 17, and 15, 16, 17 translocations have been described by other authors (4,6,22,23), but the translocation found in our patient involving four chromosomes 4, 15, 16, and 17 has not been reported before.…”
Section: Discussionmentioning
confidence: 48%
“…Variant translocation described as simple translocation involving chromosome 15 or 17 with any other chromosomes or complex translocations characterized by the involvement of additional chromosomes in addition to chromosomes 15 and 17 (4)(5)(6)(20)(21)(22)(23)(24) was found in two patients in the analyzed group. In one of them, t(11;17) (q23;q12) was identified, and in the second complex, translocation involving chromosomes 4, 15, 16, and 17 was found.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They share breakpoints between the PML and RARA genes and form a reciprocal translocation, PML–RARA and RARA–PML. This fusion induces further development of t-MN [ 61 ].…”
Section: Pathogenesis Of Therapy-related Myeloid Neoplasmmentioning
confidence: 99%
“…Some conventional methods have been reported for detection of PML/RARα, such as flow cytometry 4 , real-time quantitative reverse transcription PCR 5 , chromosome analysis 6 , fluorescence in situ hybridization 7 , 8 and microarray-based techniques 9 , etc. However, these techniques suffer from the intrinsic limitations of complicated preparation, low specificity and expensive reagent 10 , 11 .…”
Section: Introductionmentioning
confidence: 99%